2022
DOI: 10.1038/s41598-022-04916-6
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of MCL1 induces apoptosis in anaplastic large cell lymphoma and in primary effusion lymphoma

Abstract: Overexpression of antiapoptotic BCL2 family proteins occurs in various hematologic malignancies and contributes to tumorigenesis by inhibiting the apoptotic machinery of the cells. Antagonizing BH3 mimetics provide an option for medication, with venetoclax as the first drug applied for chronic lymphocytic leukemia and for acute myeloid leukemia. To find additional hematologic entities with ectopic expression of BCL2 family members, we performed expression screening of cell lines applying the LL-100 panel. Anap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
(53 reference statements)
3
2
0
Order By: Relevance
“…In contrast, both cell lines are resistant to BCL2i and BCL-xLi. These results are consistent with a study showing that PEL cell lines are sensitive to another MCL1i inhibitor AZD-5991 but are resistant to the dual BCL2/BCL-xL inhibitor ABT-263 (31).…”
Section: Primary Effusion Lymphoma Cells Are Selectively Addicted To ...supporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, both cell lines are resistant to BCL2i and BCL-xLi. These results are consistent with a study showing that PEL cell lines are sensitive to another MCL1i inhibitor AZD-5991 but are resistant to the dual BCL2/BCL-xL inhibitor ABT-263 (31).…”
Section: Primary Effusion Lymphoma Cells Are Selectively Addicted To ...supporting
confidence: 92%
“…In contrast, BCL2 expression is detectable only in BC-1 and BC-3, while we do not detect A1 or Diva in any of the cell lines. Similar expression patterns of MCL1, BCL2, and BCL-xL were recently reported in additional PEL cell lines (29). Together, our data indicate that PEL cell lines express the other BCL2 family proteins, but are selectively addicted to MCL1.…”
Section: Primary Effusion Lymphoma Cells Are Selectively Addicted To ...supporting
confidence: 88%
See 1 more Smart Citation
“…Myeloid cell leukemia-1 ( MCL1 ), a typical anti-apoptotic protein belonging to the oncogenic BCL-2 family, was originally identified in myeloid cells ( Reissig et al, 2022 ). MCL1 has been found to be overexpressed in many solid tumors, and many studies highlighted the potential importance of MCL1 as a therapeutic target ( Pereira-Castro et al, 2022 ; Quentmeier et al, 2022 ). It is worth noting that demethylzeylasteral was found to evoke the apoptosis of melanoma cells by downregulating the level of MCL1 ( Zhao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, unbiased genome wide CRISPR activation screens revealed a dominant role for A1 in venetoclax resistance in a novel model of aggressive lymphoma [ 57 ]. Furthermore, high BFL-1 levels were reported in ALCL cell lines which are resistant to MCL-1 or BCL-XL inhibitors, and siRNA knockdown of BCL2A1 induced apoptosis in drug resistant cells [ 58 ]. Finally, a study of 27 T cell lymphoma patients showed that previously chemotherapy-treated patients exhibited significantly higher levels of BCL2A1 expression compared to untreated patients [ 59 ].…”
Section: Bfl-1 In Drug Resistancementioning
confidence: 99%